2022
DOI: 10.3390/ijerph19127471
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Hamstring-to-Quadriceps Ratio and Jumping and Sprinting Abilities of Young Male Soccer Players

Abstract: The correct torque ratio between the knee joint extensor and flexor muscle groups can effectively prevent injuries to the anterior cruciate ligament and hamstring strain. However, it is unclear whether a high torque ratio of the knee joint flexor muscles to the extensor muscles is beneficial for sport performance. Therefore, the aim of the study was to investigate the relationship between the hamstring-to-quadriceps (H/Q) ratio and sprint times (10- and 30-m) and jump heights (CMJ—countermovement jump and SJ—s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…A soccer player’s quadriceps muscles affect jumping and ball-kicking as well as running abilities, and the hamstrings act as antagonists when quadriceps power occurs, controlling posture and stabilizing the knee joint during turns or tackles [ 38 , 39 ]. The results of the isokinetic knee strength assessment in this study with a peak torque of 60°/s and an average power of 180°/s showed significant improvement in both groups, and the total work at 240°/s was significantly improved only in HFG.…”
Section: Discussionmentioning
confidence: 99%
“…A soccer player’s quadriceps muscles affect jumping and ball-kicking as well as running abilities, and the hamstrings act as antagonists when quadriceps power occurs, controlling posture and stabilizing the knee joint during turns or tackles [ 38 , 39 ]. The results of the isokinetic knee strength assessment in this study with a peak torque of 60°/s and an average power of 180°/s showed significant improvement in both groups, and the total work at 240°/s was significantly improved only in HFG.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is reasonable to conclude that incorporating resistance, strength, and conditioning training during the pre-season stage into the training of young soccer players may enhance performance. Such training can serve as a stimulus for hormonal and metabolic adaptations, specifically affecting growth hormone and testosterone levels, particularly in the age groups U-16 and U-18 [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the insignificant contribution of the knee joint flexors in the vertical jump test, as pointed out in Struzik & Pietraszewski (2019) . Diker et al (2022) indicated the important role of knee joint extensors strength in sprint performance. These studies exhibited that knee joint extensor strength plays an important role in jump and sprint performance.…”
Section: Discussionmentioning
confidence: 99%